Organizational Psychological Relations of Role-Playing Ustanovkas in Double Cadres in Uzbek Families - Kaf.Senior Teacher Ruzikulova A.T (Genius Publishing Group, 2023)
The topic reflected in the article is devoted to the relationship between husband and wife The topic reflected in the article is devoted to the relationship between husband and wife. The article is intended for psychologists-researchers, employees working in the field of spirituality and enlightenment
Keywords: Relationship; psychologists-researchers; employees; working